A collage of 5 playing cards from the Metamorphoses series - McCrae, George Gordon, 1833-1927. (1870)
An arrangement of 5 playing cards. Suits include: clubs as sailors and spade as hats.
Card metamorphoses
Title from inscription on mount.
In his Album of drawings; R7997-R8402.
Mounted on heavy brown paper.
Condition: good.
Also available online
Keywords: Playing cards